Association of bovine KISS1 single nucleotide polymorphisms with reproductive traits in Indian Cattle. Issue 8 (25th June 2020) - Singh, Umesh; Alex, Rani; Kumar, Sushil; Deb, Rajib; Venkatesan Raja, Thiruvothur; Singhal, Shaily; Sengar, Gyanendra Singh; Singh Rathod, Bharat; Srirama Murthy, Kotikalapudi; Vasant Rao Patil, Nitin
Abstract: Kisspeptins, a family of neuropeptide encoded by the Kiss1 gene, have emerged as crucial regulator of fertility and reproduction by regulating the hypothalamic–pituitary–gonadal axis. The present study was aimed to identify and associate SNPs in the KISS1 gene with reproductive traits in cattle of Indian origin. DNA samples collected from 300 individual cows of three Indian dairy breeds (Gir, Kankrej and Frieswal) of cattle were used in the study. The SNPs of KISS1 gene were identified with PCR‐RFLP and sequence analysis using two sets of primer pairs. A total of 5 SNPs were identified in the targeted region of which, two were selected for screening the population and association studies. The analysis revealed that genotypes of rs442633552G>A and rs42022871C>T had a significant association with dry period. The SNP rs42022871C>T also established significant role in milk production traits, and selection of TT‐genotyped animals will improve the reproduction and production potential of the animals.